2021
DOI: 10.1111/jopr.13389
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning Zirconia Surface Prior To Bonding: A Comparative Study of Different Methods and Solutions

Abstract: Purpose To evaluate resin cement bond strength after removal of salivary contamination from a zirconia surface using different cleaning solutions and air‐borne particle abrasion. Materials and methods One‐hundred and twenty zirconia specimens (KATANA STML, Noritake) were prepared and divided into 12 groups (n = 10). Groups were subjected to a notched‐edge shear bond strength test (ISO 29022) to analyze the bonding efficiency of a resin cement (Panavia V5, Kuraray Noritake Dental Inc.) before and after contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…In addition, it is reported that phosphoric acid can react with zirconia, resulting in leaving a phosphorous residue on the zirconia surface, which would negatively affect the chemical reaction between 10-MDP molecules and zirconia and thus reduce the resin-zirconia bond strength [16,29]. It is reported that the use of phosphoric acid for cleaning of contaminated zirconia impairs resin-zirconia bonding [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it is reported that phosphoric acid can react with zirconia, resulting in leaving a phosphorous residue on the zirconia surface, which would negatively affect the chemical reaction between 10-MDP molecules and zirconia and thus reduce the resin-zirconia bond strength [16,29]. It is reported that the use of phosphoric acid for cleaning of contaminated zirconia impairs resin-zirconia bonding [22].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-sintered zirconia blocks (inCoris TZI C, Sirona Dental Systems GmbH, Bensheim, Germany) were milled into a total of 220 smaller blocks with the dimensions of 8 mm length, 8 mm width and 3 mm height using a dental milling machine (CAM 5-S1, vhf camfacture AG, Ammerbuch, Germany). The prepared zirconia blocks were sintered according to the manufacturer's instructions [22] and embedded in a self-curing acrylic resin. The top surface of zirconia specimens was polished for 2 min with 600-grit silicon carbide paper mounted on a polishing machine at a speed of 300 rpm under a water coolant and subjected to air-abrasion using 50 µm Al 2 O 3 with 2 bar air pressure for 20 s according to the manufacturer instructions [22], followed by ultrasonic cleaning in distilled water for 5 min, and subsequently air-dried.…”
Section: Zirconia Specimen Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Saliva contamination is therefore a significant issue in zirconia bonding. A recent study by Sulaiman et al 41 compared non-contaminated zirconia samples with various methods of saliva decontaminations. They found that air-borne particle abrasion after saliva contamination is perhaps the most effective method to decontaminate saliva from the zirconia surface providing the highest bond strength.…”
Section: Luting Cements and Cementation Proceduresmentioning
confidence: 99%